A technology forecasting by analogy and industry analysis for the SAP enterprise resource planning acquisition system of CBK Power Limited - Acain, Hans Arvin M. (University of the Philippines Diliman, 2009)
The research discusses the competitive advantages of Enterprise Resource Planning (ERP) systems and the benefits that the acquiring company can harvest from its implementation. Laid within the initial pages of the research are the following : a brief background of CBK Power Limited, its current rebuilding status, the goals and objectives of the company concerning finding a key technological solution that will fit the framework of the company's day to day operations. The conceptual framework used the research made sure that the proposed evaluation of the ERP system fit perfectly with its ISO 9001 Integrated Management Systems. The evaluation of the technology utilized Technology Forecasting by Analogy with a Fortune 50 company as well as Industry Analysis using industry specific interviews, internet research as well as SAP sponsored white papers. A review of related literature detailed the competitive gains from ERP systems. Detailed are methods for define and measure the current competitiveness of the company that will acquire the technology as well as the necessary steps on ensuring the success of the ERP's implementation. The review of related literature focused on the ERP's inherent behavior of integrating technology management concepts such as knowledge management, project management, technology forecasting and technology acquisition and assimilation. Industry interviews detailed some interesting areas involving process innovation-a key concept that companies expect to gain upon the acquisition of ERP systems. The research derived that ERP systems are increasingly a requirement for organizations just to stay competitive. Additionally, the research suggests that an ERP system can yield at most a temporary competitive advantage as others are also installing these enterprise-wide systems. Focusing on the achievement of competitive advantage through ERP, acquiring companies highlight the fact that ERP systems as one of the major motives of firms attaining a competitive advantage. Technology forecasting by analogy and industry analysis done by the researcher reflected the differences in the economic and managerial approaches between the Fortune 50 Company and CBKPL. While it was derived that while there is an inherent competitive advantage obtained from the acquisition from ERP systems and that CBK Power Limited would largely benefit from its implementation, must change its management approach of the project as the company's internal resources will have a hard time prioritizing between work and the project. There is also a lingering threat that the project proponents will feel unappreciated and left out, as a rewards system for the timeliness and successful implementation of the project is absent.